BRD7 expression and c-Myc activation forms a double-negative feedback loop that controls the cell proliferation and tumor growth of nasopharyngeal carcinoma by targeting oncogenic miR-141 - Yukun Liu; Ran Zhao; Yanmei Wei; Mengna Li; Heran Wang; Weihong Niu; Yao Zhou; Yuanzheng Qiu; Songqing Fan; Yihao Zhan; Wei Xiong; Yanhong Zhou; et al. (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract Background miR-141 is up-regulated and plays crucial roles in nasopharyngeal carcinoma (NPC). However, the molecular mechanism underlying the dysregulation of miR-141 is still obscure. Methods Thus, the ChIP-PCR was performed to identify the c-Myc-binding sites in miR-141 and BRD7. qRT-PCR, western blot and immunohistochemistry assays were used to detect the expression of miR-141 and its up/down stream molecules. The rescue experiments on the c-Myc/miR-141 axis were performed in vitro and in vivo. Results Our results showed that the levels of mature miR-141, pre-miR-141 and pri-miR-141 were downregulated in c-Myc knockdown NPC cells. Meanwhile, c-Myc transactivates the expression of miR-141 by binding its promoter region. Moreover, BRD7 was identified as a co-factor of c-Myc to negatively regulate the activation of c-Myc/miR-141 axis, as well as a direct target of c-Myc. Moreover, restoration of miR-141 in c-Myc knockdown NPC cells notably rescued the effect of c-Myc on cell proliferation and tumor growth, as well as the blocking of PTEN/AKT pathway. Additionally, the expression of c-Myc was positively correlated with that of miR-141 and the clinical stages of NPC patients and negatively associated with the expression of BRD7. Our findings demonstrated that BRD7 expression and c-Myc activation forms a negative feedback loop to control the cell proliferation and tumor growth by targeting miR-141. Conclusions These observations provide new mechanistic insights into the dysregulation of miR-141 expression and a promising therapeutic option for NPC.